Studi Kemampuan Adsorpsi Ion Logam Cr6+ oleh Tanah Vulkanik Ã¢â‚¬Å“Studi Kasus Wilayah Industri Penyamakan Kulit, GarutÃ¢â‚¬Â - Sumawijaya, Nyoman; Mulyono, Asep; Rusydi, Anna Fadliah (Jurnal Teknologi Lingkungan, 2020)
ABSTRACTThe leather tanning industry in Sukaregang, Garut Regency, produces liquid waste containing Chromium and is discharged directly into the Ciwalen River without a waste treatment process. The content of Cr6+ as metal ions in the waste can also contaminating groundwater. The movement of Cr6+ will pass through the soil media before entering to the groundwater wells. The capability of the soil to adsorb the contaminant will reduce the impact on groundwater. The purpose of this study was to determine the ability of the soil in adsorbing and inhibiting the movement of Cr6+ into groundwater. The study was carried out at Sukaregang, Garut Regency and conducting adsorption experiments with a batch system. The analysis was carried out using the Langmuir and Freundlich isotherm model. The experimental results showed that Cr6+ adsorbed ranged from 38% to 57% of the initial concentration. The results from Langmuir Isotherm were: the distribution coefficient (Kads) was 0.45 L/mg and the maximum adsorption capacity (qm) was 2.44 mg/100g sorbent with R2 = 0.959 and Freundlich Isotherm was: qm was 2,86 mg/100g sorbent and Kads was 0,35 L/mg with R2 = 0,860. This large adsorption capacity is caused by soil texture and soil organic content. The soil in Sukaregang tanning industries has a high adsorption capacity towards Cr6+ contaminants.Keywords: adsorption, chromium, Cr6+, contaminant, volcanic soil, GarutABSTRAKIndustri penyamakan kulit di wilayah Sukaregang, Kabupaten Garut, menghasilkan limbah cair yang mengandung Kromium dan dibuang ke Sungai Ciwalen tanpa proses pengolahan limbah. Kandungan ion logam Cr6+ pada limbah dapat mencemari air tanah. Pergerakan ion logam Cr6+ akan melalui media tanah sebelum memasuki sumur-sumur penduduk. Beberapa jenis tanah mempunyai kemampuan untuk mengadsorpsi ion pencemar sehingga tidak semua limbah yang meresap ke dalam tanah mencemari air tanah. Tujuan dari penelitian ini adalah untuk mengetahui peranan tanah dalam menghambat pergerakan ion logam Cr6+ ke dalam air tanah. Penelitian dilaksanakan dengan pengambilan sampel tanah di daerah Sukaregang, Garut, dan melakukan percobaan adsorpsi dengan sistem batch. Sementara analisis dilakukan dengan menggunakan model isotherm Langmuir dan Freundlich. Hasil percobaan menunjukkan konsentrasi Cr6+ yang teradsorpsi berkisar 38 – 57 % dari konsentrasi awal. Kads sebesar 0,45 L/mg dan qm sebesar 2,44 mg/100g tanah dengan nilai R2 = 0,959 menggunakan isoterm Langmuir dan isoterm Freundlich memberikan nilai qm sebesar 2,86 mg/100 g sorbent dan Kads sebesar 0,35 L/mg dengan R2 = 0,860. Tingginya daya adsorpsi ini disebabkan oleh tekstur tanah dan kandungan bahan organik. Tanah di wilayah penelitian memiliki daya adsorpsi yang besar terhadap kontaminan Cr6+.Kata kunci: adsorpsi, kromium, Cr6+, kontaminan, tanah vulkanik, Garut